Analisis Hukum Pengelolaan Dana Desa Dalam Pemilihan Kepala Desa di Kabupaten Donggala - Friskanov. S, Irzha (Fakultas Syariah INSURI Ponorogo, 2023)
Village funds are an important tool for the village government in carrying out village development initiatives, one of which is the election of the village head. Democracy in the context of village head elections (Pilkades) can be interpreted as an acknowledgment of the diversity of society and participatory political views in the context of village democratization. Elections for village heads are direct, general, free, confidential, honest and fair, which is interpreted as an acknowledgment of the diversity of political views. The problem is how to analyze the law in managing village funds in the village head election in Donggala Regency. This study uses normative legal research using statutory approaches, conceptual approaches, and case approaches. With the conclusion that village fund management has a significant influence on the success of the village head election committee. The village community apart from implementing it is also a determining factor in the success of oversight in the management of village funds. Apart from being able to answer the needs of the community, village funds are also able to play an important role in village development in realizing justice and prosperity for village communities.